2013
DOI: 10.1371/journal.pone.0056944
|View full text |Cite|
|
Sign up to set email alerts
|

Disease Activity in Inflammatory Bowel Disease Is Associated with Increased Risk of Myocardial Infarction, Stroke and Cardiovascular Death – A Danish Nationwide Cohort Study

Abstract: PurposeChronic inflammatory diseases have been linked to increased risk of atherothrombotic events, but the risk associated with inflammatory bowel disease (IBD) is unclear. We therefore examined the risk of myocardial infarction (MI), stroke, and cardiovascular death in patients with IBD.MethodsIn a nationwide Danish population-based setting, a cohort of patients with incident IBD between 1996 and 2009 were identified in national registers. Hospitalizations with IBD as primary diagnosis, initiation of biologi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

10
174
4
14

Year Published

2014
2014
2023
2023

Publication Types

Select...
9
1

Relationship

2
8

Authors

Journals

citations
Cited by 204 publications
(202 citation statements)
references
References 39 publications
10
174
4
14
Order By: Relevance
“…Although the studied groups were not completely comparable in demographical and comorbidity features, the authors reported a higher prevalence of ischemic stroke in IBD patients (mainly in CD patients) than the general population (hazard ratios for UC and CD were 1.01 [95% conidence interval = 0.84-1.21] and 1.15 [95% conidence interval = 1.04-1.28], respectively) [24]. Similar results were reported in a Danish population-based seting (also with a mismatch in comorbidity distribution), showing a relative risk (RR) of 1.15 of sufering ischemic stroke in an IBD population (95% conidence interval 1.04-1.27) of sufering ischemic stroke in an IBD population [25]. Therefore, there is weak evidence of the higher incidence of ischemic stroke in IBD populations.…”
Section: Venous and Arterial Thrombotic And Thromboembolic Manifestatsupporting
confidence: 79%
“…Although the studied groups were not completely comparable in demographical and comorbidity features, the authors reported a higher prevalence of ischemic stroke in IBD patients (mainly in CD patients) than the general population (hazard ratios for UC and CD were 1.01 [95% conidence interval = 0.84-1.21] and 1.15 [95% conidence interval = 1.04-1.28], respectively) [24]. Similar results were reported in a Danish population-based seting (also with a mismatch in comorbidity distribution), showing a relative risk (RR) of 1.15 of sufering ischemic stroke in an IBD population (95% conidence interval 1.04-1.27) of sufering ischemic stroke in an IBD population [25]. Therefore, there is weak evidence of the higher incidence of ischemic stroke in IBD populations.…”
Section: Venous and Arterial Thrombotic And Thromboembolic Manifestatsupporting
confidence: 79%
“…Currently, the reported results for the risk of CV disease in the setting of IBD have been ambiguous, with some studies revealing an increased risk of both ischemic heart disease and cerebrovascular accidents and others showing no associations [25][26][27][28]. Additionally, a few studies have suggested that IBD patients have a lower burden for some traditional risk factors for CV disease, such as HT, DM, dyslipidemia and obesity, and that nontraditional risk factors may play an important role in IBD patients [28,29].…”
Section: Discussionmentioning
confidence: 99%
“…A retrospective study from North America [16] showed that the incidence of coronary artery disease in patients with IBD was higher as compared to a control group, in spite of a low incidence of traditional risk factors (smoking, diabetes, hypertension and hypercholesterolemia). Two Danish nation-wide cohort studies demonstrated an increased risk of ischemic heart disease and also showed that the risk was lower in those treated with 5-ASA [17,20]. Finally, a systematic review has confirmed the key role of chronic inflammation in causing progression of the atherosclerotic process and thus, coronary risk in IBD [19].…”
Section: Introductionmentioning
confidence: 88%